Struktur Anatomi Batang Langsat (Lansium domesticum Corr.) yang Terserang Penyakit Kanker Batang - Riza Linda, Karina Putri Defianti Mukarlina (Universitas Tanjungpura, 2015)
Stem canker is a plants disease caused by infection of Phytophtora palmivora fungi on stems, branches, and twigs of plants. This canker disease can decrease the fruits productivity of langsat (Lansium domesticum). This research was aimed to observe the stem anatomical structure of langsat plants on seedling, sapling, pole, and tree level which are infected by stem canker disease. This research have been done at May until September 2014. Paraffin method was used to make cross section sample preparation of the langsat stem. The result of this research shows that there are differences on stem anatomical structure between normal langsat plants and infected plants. The results of anatomical observation showed that the tree with stem canker at every growth level had thicker dermal tissue, thicker cortex with irregular shape, thinner phloem layer, and bigger xilem cell’s pores with no shapes change. Dermal tissue at tree level got 3,1 times thicker than any other growth level of the plants.